2007
DOI: 10.1007/bf02932111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence ofBartonella DNA in ixodid ticks in Czechia

Abstract: We report the development of a novel method for detection of Bartonella DNA in ixodid ticks. The assay is based on a specific amplification of a part of 16S rRNA gene and 16S-23S rRNA intergenic spacer region of Bartonella sp. by nested PCR and Southern blot hybridization with specific DNA probe; the method is highly sensitive and specific. The screening of 327 unfed ticks collected in different urban and suburban areas of Czechia in 2003-2005 revealed the presence of Bartonella DNA in four Ixodes ricinus indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Transmission by other arthropods, in particular ticks, has been suggested: B. henselae DNA was detected in questing Ixodes paci- (Chang et al, 2001;Hercik et al, 2007;Rar et al, 2005), and in I. ricinus and Dermacentor ticks feeding on people or domestic animals in Central Europe (Sanogo et al, 2003;Podsiadly et al, 2007;Angelakis et al, 2010). Our own data revealed that B. henselae DNA was present in up to ∼40% in tick populations sampled in 4 sites in Europe (Dietrich et al, 2010).…”
Section: Cat Scratch Diseasementioning
confidence: 82%
“…Transmission by other arthropods, in particular ticks, has been suggested: B. henselae DNA was detected in questing Ixodes paci- (Chang et al, 2001;Hercik et al, 2007;Rar et al, 2005), and in I. ricinus and Dermacentor ticks feeding on people or domestic animals in Central Europe (Sanogo et al, 2003;Podsiadly et al, 2007;Angelakis et al, 2010). Our own data revealed that B. henselae DNA was present in up to ∼40% in tick populations sampled in 4 sites in Europe (Dietrich et al, 2010).…”
Section: Cat Scratch Diseasementioning
confidence: 82%
“…have mostly been identified by PCR using primers targeting either specific Bartonella genes like the citrate synthase gene ( glt A) gene, the riboflavin synthase gene, the heat shock protein gene ( gro EL), the 16S–23S intergenic spacer, the heme binding protein gene, and the cell division protein gene or the 16S rDNA gene (Table 1). Summarized results indicate that the proportion of ticks harboring Bartonella DNA can vary from low prevalences of 0.43% among questing A. americanum ticks examined in the southeastern United States ( 3 ) and 1.2% of I. ricinus ticks collected in the Czech Republic ( 24 ) to a prevalence as high as 60% in I. ricinus ticks from roe deer in the Netherlands ( 20 ) (Table 1). Bartonella spp.…”
Section: Host Associations and Specificitymentioning
confidence: 99%
“…ticks. The prevalence of Bartonella-infected ticks can vary from 1.2 % in the Czech Republic to 60 % in the Netherlands (Schouls et al, 1999;Hercik et al, 2007). Recently, I. ricinus ticks were demonstrated to be a competent vector for B. henselae (Cotte et al, 2008).…”
Section: Bartonellamentioning
confidence: 99%